The Relationship Between Parents’ Knowledge and Their Participation in the Delima Jorong Karya Harapan Posyandu in Dharmasraya Regency - Ravika Virnanda; Setiawati Setiawati (Universitas Negeri Padang, 2026)
This study was motivated by the low level of parental participation in Posyandu. One possible cause of this phenomenon is parents’ lack of knowledge about Posyandu. This study aims to (1) describe parents’ knowledge of Posyandu; (2) describe parents’ participation in Posyandu activities; (3) analyze the relationship between parents’ knowledge and their participation at the Delima Jorong Karya Harapan Posyandu, Dharmasraya Regency. This is a quantitative study with a correlational design. The study population consisted of 42 mothers registered at the Delima Jorong Karya Harapan Posyandu in Dharmasraya Regency. The sample was selected using the Slovin formula, resulting in 30 participants chosen through simple random sampling. The data analysis techniques used were percentages and the Spearman Rank formula. The results of the study indicate that (1) the description of parents’ knowledge regarding the Posyandu at the Delima Jorong Karya Harapan Posyandu in Dharmasraya Regency falls into the “low” category. This is evidenced by the fact that the majority of respondents’ answers were “incorrect” for all indicators. (2) The profile of parental participation at the Delima Jorong Karya Harapan Posyandu in Dharmasraya Regency falls into the “low” category. This is evidenced by the fact that the majority of respondents’ answers were “disagree” for all indicators. (3) There is a significant association between parents’ knowledge and their participation at the Delima Jorong Karya Harapan Posyandu in Dharmasraya Regency. This is indicated by the fact that the calculated p-value is greater than the critical p-value.